A Nationwide Study Comparing Knowledge and Beliefs about HPV among Female Students before and after HPV Vaccination - Wong, Li Ping; Alias, Haridah; Sam, I-Ching; Zimet, Gregory D. (Elsevier, 2019)
Study Objective: To assess the knowledge and beliefs regarding human papillomavirus (HPV) and the HPV vaccine among girls before and after vaccination in the Malaysian HPV Immunisation Programme. Design: A nationwide longitudinal survey. Setting: Thirty-two randomly selected schools from 13 states and 3 federal territories in Malaysia from February to March 2013, and October to November 2013. Participants: Form One female students (13 years old). Interventions: None. Main Outcome Measures: Mean knowledge score of HPV infection. Results: A total of 2644 students responded to the prevaccination survey, of whom 2005 (70%) completed the postvaccination survey. The mean knowledge score was 2.72 (SD ± 2.20) of a maximum score of 10 in the prevaccination survey, which increased significantly to 3.33 (SD ± 1.73) after the 3 doses of HPV vaccine (P = .001). Many answered incorrectly that, “Only girls can get HPV infection” (91.5%, n = 1841 prevaccination vs 96.1%, n = 1927 postvaccination), and only a few were aware that, “Vaccinating boys helps to protect girls against HPV infection” (11.4%, n = 229 for prevaccination vs 10.2%, n = 206 for postvaccination). The mean knowledge score was significantly higher postvaccination among higher-income families and those with parents of a higher occupational status. Regarding beliefs about the HPV vaccine, 89.4% in the prevaccination survey held the view that they would not get a HPV infection, and the percentage remained similar in the postvaccination survey. Perceived severity of HPV infection also remained low in the pre- and postintervention groups. Only 21.5% reported receiving health information about HPV along with the provision of the HPV vaccine; those who received health information showed higher levels of knowledge. Conclusion: Findings revealed a general lack of knowledge and erroneous beliefs about HPV and the HPV vaccine even after receiving vaccination. This suggests that imparting accurate knowledge about HPV along with vaccine administration is essential. Specifically, girls from lower socioeconomic groups should be a target of educational intervention. © 2018 North American Society for Pediatric and Adolescent Gynecology